Sociabilidades e enobrecimento: o bairro Treze de Julho em Aracaju. - Rabelo, Josevânia Nunes (2010)
This work aimed to survey the Treze de Julho quarter, by the study of the urban usage and its setup, so to understand if we have, in Aracaju a Neighborhood configured by a gentrification policy of residential kind. In the past the Treze de Julho Neighborhood was a popular seaside beach. In that space, the aracajuanos lived experiences of encounters with fishermen, in a pace set by the nature. In the romantic beach, where fishermen, metallurgists lived and, alternately, the summerer vacationists seeking some rest of the urban centre incipient unrest. It was, therefore, a place for entertainment and communitarian sociabilities, which was broken by the passage of the privileged social stratum from downtown and surroundings areas to the coastal south zone. The urban growth and its modernity icons, represented by an at any cost progress, that couldn‟t keep the bath beach and, besides, banished most of the old residents. Today, instead of the beach we see the mangrove, serving as a filter to the urban wastes. In parallel, in order to hide the environment degradation a Sidewalk was built, and in front of it we have the luxurious buildings of the Beira Mar Avenue. To fully understand the consequences of the transformations to the residents and the construction of new types of sociabilities in the Neighborhood, direct observations was made, delimiting three distinct areas, each one presenting distinct characteristics. The first zone is still formed by the remaining old residents. The second one was configured by the residents of the luxurious buildings and the elegant stores. And in the third one there are the ways of usage provided by the Viana de Assis Sidewalk, which distorts the linearity of that urban space, that was projected to be a redoubt for the elite of the Neighborhood. Being so, in the Neighborhood, was established a social-spatial segregation interlacing as one more dynamics in the diversified uses of the Viana de Assis Sidewalk. It was observed that the image of a Neighborhood delimited by rigid borders, it can be dissolved into the flowed zone of the mangrove spill. There, the agents can stroll and offer a distinct noise for the noble Neighborhood.